2021
DOI: 10.3390/ijms22083999
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Proteasome in Platelet Function

Abstract: Platelets are megakaryocyte-derived acellular fragments prepped to maintain primary hemostasis and thrombosis by preserving vascular integrity. Although they lack nuclei, platelets harbor functional genomic mediators that bolster platelet activity in a signal-specific manner by performing limited de novo protein synthesis. Furthermore, despite their limited protein synthesis, platelets are equipped with multiple protein degradation mechanisms, such as the proteasome. In nucleated cells, the functions of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 180 publications
0
8
0
Order By: Relevance
“…Fibrinogen is a 340-kDa plasma glycoprotein mainly synthesized by liver parenchymal cells [14,15]. The protein is also stored in the platelet alpha granules, thus providing a localized boost in fibrinogen concentration at sites of platelet activation [16]. Fibrinogen is synthetized as a hexamer composed of two copies of three homologous polypeptide chains (Aα, Bβ, and γ), interconnected by a complicated series of disulfide bonds [1,9].…”
Section: Structure and Function Of Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinogen is a 340-kDa plasma glycoprotein mainly synthesized by liver parenchymal cells [14,15]. The protein is also stored in the platelet alpha granules, thus providing a localized boost in fibrinogen concentration at sites of platelet activation [16]. Fibrinogen is synthetized as a hexamer composed of two copies of three homologous polypeptide chains (Aα, Bβ, and γ), interconnected by a complicated series of disulfide bonds [1,9].…”
Section: Structure and Function Of Fibrinogenmentioning
confidence: 99%
“…A case study also described the successful use of a new oral anticoagulant (rivaroxaban) for the anticoagulant management in patient with afibrinogenemia and severe hypofibrinogenemia [12,88]. The treatment of thrombotic episodes is very demanding due to the high risk of bleeding [5,16]. Further studies are required to determine the optimal postoperative thromboprophylaxis in CFD.…”
Section: Management Of Thrombotic Complicationsmentioning
confidence: 99%
“…Platelets, like nucleated cells, have an active proteasome system [23,24]. Earlier, a study by Ostrowska et al showed that the human platelet 20S proteasome has a chymotrypticlike activity [25].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a global proteomic analysis has shown that platelets express all the three proteolytic activities of the proteasome: caspase-like, trypsin-like and chymotrypsin-like activities [26]. Although the role of platelet proteasome in protein degradation is not clear [23], its role in regulating platelet production [27] and lifespan [28] has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are acellular fragments derived from maturing megakaryocytes and function mainly in maintaining primary hemostasis and thrombosis to preserve vascular integrity ( 219 ). Although predominated by platelets—reservoirs of multitudinous immunologic molecules, soluble proteins, and growth factors ( 220 )— and plasma components, PRP contains cellular components, such as leukocytes ( 217 ). Several commercially available kits can be used for PRP processing with varying outcomes in terms of platelet, red blood cell, and leukocyte concentrations ( 221 ).…”
Section: Acellular Therapies With Multicellular Componentsmentioning
confidence: 99%